Higgs pair production at the LHC in models with universal extra dimensions - de Sandes, H. [UNESP]; Rosenfeld, Rogério [UNESP] (Elsevier B.V., 2008)
In this Letter we study the process of gluon fusion into a pair of Higgs bosons in a model with one universal extra dimension. We find that the contributions from the extra top quark Kaluza-Klem excitations lead to a Higgs pair production cross section at the LHC that can be significantly altered compared to the Standard Model value for small values of the compactification scale. (C) 2007 Elsevier B.V. All rights reserved.